Narrative structure, symbolic meaning, and cultural expression in contemporary Indonesian horror cinema - Abidin, Zainal; Riski, Wahyu Nova; Barry, Syamsul (International Journal of Visual and Performing Arts, 2025)
This study investigates narrative strategies in contemporary Indonesian horror films to understand how they convey cultural meanings and engage audiences. While horror is often dismissed as entertainment, Indonesian horror serves as a cultural mirror, reflecting societal fears, spiritual beliefs, and identity struggles. The study focuses on eight films released between 2019 and 2024, selected for their narrative complexity, cultural relevance, and critical reception. Using qualitative narrative analysis, the research applies Seymour Chatman's distinction between story and discourse alongside classical and modern narrative theories by Bordwell, Todorov, Genette, and others. The analysis identifies three-act and five-act structures and nonlinear, circular, and episodic narratives. These structures enhance suspense, emotional engagement, and thematic depth. The findings show that Indonesian horror films blend local folklore, Islamic rituals, and communal values with experimental storytelling. For example, Siksa Kubur uses fragmented timelines to depict trauma, while Qodrat integrates religious exorcism into its plot structure. Such strategies deepen audience immersion and articulate culturally specific anxieties. This research contributes to Indonesian cinema studies by highlighting how narrative form shapes meaning and emotional impact. It offers a framework for analyzing horror beyond Western paradigms and provides insights into how traditional and modern storytelling coexist in Southeast Asian media. Academically, it advances narrative theory in a non-Western context. Practically, it supports filmmakers and cultural producers in using horror to engage with social issues and connect with global audiences through culturally grounded storytelling.